Incorporating connectivity into conservation planning for the optimal representation of multiple species and ecosystem services. Issue 4 (11th August 2020) - Williams, Sara H.; Scriven, Sarah A.; Burslem, David F. R. P.; Hill, Jane K.; Reynolds, Glen; Agama, Agnes L.; Kugan, Frederick; Maycock, Colin R.; Khoo, Eyen; Hastie, Alexander Y. L.; Sugau, John B.; Nilus, Reuben; et al.
Abstract: Conservation planning tends to focus on protecting species' ranges or landscape connectivity but seldom both—particularly in the case of diverse taxonomic assemblages and multiple planning goals. Therefore, information on potential trade‐offs between maintaining landscape connectivity and achieving other conservation objectives is lacking. We developed an optimization approach to prioritize the maximal protection of species' ranges, ecosystem types, and forest carbon stocks, while also including habitat connectivity for range‐shifting species and dispersal corridors to link protected area. We applied our approach to Sabah, Malaysia, where the state government mandated an increase in protected‐area coverage of approximately 305, 000 ha but did not specify where new protected areas should be. Compared with a conservation planning approach that did not incorporate the 2 connectivity features, our approach increased the protection of dispersal corridors and elevational connectivity by 13% and 21%, respectively. Coverage of vertebrate and plant species' ranges and forest types were the same whether connectivity was included or excluded. Our approach protected 2% less forest carbon and 3% less butterfly range than when connectivity features were not included. Hence, the inclusion of connectivity into conservation planning can generate large increases in the protection of landscape connectivity with minimal loss of representation of other conservation targets. Abstract : Article impact statement : New protected‐area design in Sabah, Borneo, reveals that connectivity can be used in planning without compromising other conservation goals. Abstract : Incorporación de la Conectividad a la Planeación de la Conservación para la Representación Óptima de Especies Múltiples y Servicios Ambientales Resumen: Las tendencias de planeación de la conservación tienden a enfocarse en la protección de la distribución geográfica de las especies o en la conectividad de paisajes, pero rara vez se enfocan en ambas – particularmente para el caso de los ensamblajes taxonómicos y las metas múltiples de planeación. Por lo tanto, hay carencias en la información sobre las compensaciones potenciales entre mantener la conectividad de los paisajes y alcanzar otros objetivos de conservación. Desarrollamos una estrategia de optimización para priorizar la protección máxima de la distribución de las especies, los tipos de ecosistemas y los stocks de carbono de los bosques, a la vez que incluimos la conectividad del hábitat para las especies que modifican su distribución y los corredores de dispersión para conectar el área protegida. Aplicamos nuestra estrategia en Sabah, Malasia, en donde el gobierno estatal ordenó un incremento de ∼305, 000 ha en la cobertura de áreas protegidas sin especificar la ubicación de las nuevas áreas protegidas. En comparación con una estrategia de planeación de la conservación que no incorporó las dos características de la conectividad, nuestra estrategia incrementó la protección de los corredores de dispersión y la conectividad altitudinal en un 13% y 21% respectivamente. La cobertura de la distribución de las especies de plantas y vertebrados y de los tipos de bosque fue la misma con o sin la inclusión de la conectividad. Nuestra estrategia protegió 2% menos del carbono forestal y 3% menos de la distribución de mariposas que cuando no se incluyeron las características de conectividad en la estrategia. Por lo tanto, incluir a la conectividad en la planeación de la conservación puede generar grandes incrementos en la protección de la conectividad del paisaje con una pérdida mínima de representación para los demás objetivos de conservación.